Kepatuhan ibu pada masa kehamilan, persalinan, dan nifas dalam pelaksanaan program pencegahan penularan HIV - Sri Wahyuni (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
This research aim is to explore the  adherence of mother during the PPIA programme. Qualitative metodhe was used especially with explanatory research. Purposive sampling continued with snowball sampling was used. Results from this study is the third of five informants did not comply with PPIA. During labour, R4 giving birth in community health center. While R1,R2,R5 already adherence gave birth at Hospital Dr. Sardjito. The examination results VCT and Viral Load for children R1, R3, and R5 can be demonstrated to children not infected with HIV by her mother. For children of R4 is already infected with HIV by her mother because it did not comply with the PPIA. For children from R3 can not be proven contracting or not because it is still in gestation.